Damage caused by animals in light of the provision of Article 431 of the Civil Code - Piernik-Wierzbowska, Kamila (Studia Iuridica Toruniensia, 2021)
The use of animals or raising animals necessitates a particular type of conduct both towards animals as well as the surrounding. Animals, as living organisms, do not totally succumb to the will and management of the human being and pose a heightened risk to the environment they find themselves in. This aspect has led to the introduction in Article 431 of the Civil Code of heighten liability based on the presumption of fault in supervision. It is noticeable in case law that this liability is narrowed to instances where the animal caused damage totally and solely due to its own instinctive drive, which narrowing is inconsistent with the purpose of the regulation and is not justified.